IMPLEMENTATION OF THE SIGNAL APPLICATION IN SUPPORTING E-GOVERNMENT IN MOTOR VEHICLE TAX SERVICES AT SAMSAT DENPASAR CITY - Yumita Lestari; I Kadek Dede Junaedy; Ni Luh Putu Ening Permini (Jurnal Widya Publika, 2026)
This study aims to analyze the implementation of the SIGNAL application in supporting e-government for motor vehicle tax services at SAMSAT in Denpasar City. This study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. The research analysis employs George C. Edward III’s policy implementation theory, which encompasses the aspects of communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of the SIGNAL application has been quite optimal. Regarding communication, information dissemination is conducted through public outreach, social media, the official website, and direct services. The resources aspect demonstrates the availability of adequate infrastructure and human resources. Regarding disposition, employees demonstrated a positive attitude and commitment to supporting digital services. Furthermore, the bureaucratic structure has operated in an organized and collaborative manner across agencies. However, the implementation of the SIGNAL application has not yet been fully optimal due to the challenge of low digital literacy among the public, resulting in uneven understanding of the application’s use among motor vehicle taxpayers. Keywords: Implementation, SIGNAL Application, E-Government